ANALISIS PROFIL SENYAWA KIMIA MINYAK ALPUKAT DARI DUA VARIETAS BUAH ALPUKAT (Persea americana) DAN POTENSINYA UNTUK KESEHATAN - Winarni, Sri; Mustafa, Annasari; Kurniawati, Atik (Poltekkes Kemenkes Bandung, 2024)
Avocado (Persea americana) is a popular tropical fruit due to its health benefits and its diverse applications in culinary and cosmetic industries. The avocado fruit is not only consumed for its flesh, but its utilization has now expanded with the production of avocado oil. As interest in avocado oil increases, different extraction methods have been developed to obtain oil of the highest quality. This study aimed to analyze the chemical profile of avocado oil from two varieties, as well as evaluate its health potential. The research method used is descriptive, focusing on the composition of fatty acids analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). The results of the study showed that the butter variety avocado oil contains fatty acids such as tetracosanoic acid, octadecenoic acid, undecylenic acid, palmitic acid, nonanoic acid, and heptacosanoic acid. Meanwhile, the alligator variety avocado oil contains fatty acids such as oleic acid and linoleic acid. The study concluded that variations in avocado fruit influence the fatty acid composition of avocado oil extracted by the autoclave method, where alligator variety avocado oil provides health benefits as a source of vegetable oil rich in oleic and linoleic acids, while the butter variety avocado oil offers benefits for nerve health. Recommendations for further research include clinical studies evaluating the health benefits of avocado oil, with a focus on the effects of fatty acids such as tetracosanoic acid, oleic acid, and linoleic acid, to provide stronger scientific evidence regarding their effects on nerve, heart, and skin health.